2017
DOI: 10.1007/s00520-017-3902-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body composition on outcome in patients with early breast cancer

Abstract: PurposeWe investigated the impact of body composition on outcomes of patients with early breast cancer. Skeletal muscle mass, visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), and muscle fat infiltration or inter-muscular adipose tissue areas (IMAT), obtained by computed tomography (CT), were assessed.MethodsA total of 119 female patients who had breast cancer were included in this retrospective study. The total skeletal muscle and fat tissue areas were evaluated in two adjacent axial slices ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 34 publications
4
103
0
3
Order By: Relevance
“…These results show that ultra-processed food consumption and overweight were associated with breast cancer in this sample of Brazilian women, which is partially consistent with published studies [5,7,21,22]. Additionally, poor environmental sanitation and family history of cancer were identified as risk factors for breast cancer in these women.…”
Section: Discussionsupporting
confidence: 91%
“…These results show that ultra-processed food consumption and overweight were associated with breast cancer in this sample of Brazilian women, which is partially consistent with published studies [5,7,21,22]. Additionally, poor environmental sanitation and family history of cancer were identified as risk factors for breast cancer in these women.…”
Section: Discussionsupporting
confidence: 91%
“…The cutoff points used for classifying BCPs were based on data in the literature. 6,8 Radiologists, who performed the BCPs measures, were blinded for clinical data. We evaluated subcutaneous fat area (SFA, cm 2 ), visceral fat area (VFA, cm 2 ), lumbar muscle crosssectional area (LMCA, m 2 ) and liver steatosis (L/S ratio).…”
Section: Body Composition Parameters (Bcps)mentioning
confidence: 99%
“…38 The smallest study (n=119) found similar results with sarcopenia (defined as skeletal muscle index < 41 cm2/m2 measured on CT) significantly associated with worse disease free (p=0.02) and overall (p=0.05) survival, whereas there was no significant association between BMI and survival. 39 …”
Section: Association With Cancer Recurrence and Survivalmentioning
confidence: 99%